2018
DOI: 10.1039/c8qm00436f
|View full text |Cite
|
Sign up to set email alerts
|

Ni-modified Ti3C2MXene with enhanced microwave absorbing ability

Abstract: Ni-modification of Ti3C2MXene enables enhanced microwave absorption ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Ti 3 C 2 T x is a representative of MXene family decorated with abundant active surface functional terminations [27][28][29], which could provide remarkable amount of dipolar and interfacial polarizations. Moreover, the variety surface terminations of MXene by ion intercalation [30], annealing [31], and oxidization [32] could offer tunable EMW absorbing properties. In general, EMW absorbers should have strong EM energy attenuation ability and moderate conductivity for impedance matching.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 3 C 2 T x is a representative of MXene family decorated with abundant active surface functional terminations [27][28][29], which could provide remarkable amount of dipolar and interfacial polarizations. Moreover, the variety surface terminations of MXene by ion intercalation [30], annealing [31], and oxidization [32] could offer tunable EMW absorbing properties. In general, EMW absorbers should have strong EM energy attenuation ability and moderate conductivity for impedance matching.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, two researcher groups, han, coworkers, and shahzad et al, reported the EMI shielding study on the MXene that established the 2D Mxene as the versatile material for EMI shielding application162,163 . Feng et al studied the Ni-modified Ti 3 C 2 MXene in the frequency range of 2-18 GHz164 . The effective absorbing bandwidth is greatly broadened, especially at the lower frequency of 2-8 GHz.…”
mentioning
confidence: 99%
“…The magnetic properties of Fe 3 O 4 @TiO 2 -Ti 3 C 2 T x MXene nanocomposite were explained elsewhere [17,18]. The RL (dB) of a perfect electric conductor (PEC)-backed material (figure 2a) can be expressed as [12][13][14][15][16][17][18][19] reflection loss (RL) ¼ 20log…”
Section: Resultsmentioning
confidence: 99%
“…MXene has been particularly noted by the scientific community in the last 8 years for its unique structure and electrical properties [12][13][14]. MXene's utilization for microwave absorption is increasing day by day; however, the understanding of its contribution is only related to its metal-like properties and surface-rich functional groups [1,[11][12][13][14][15][16][17][18]. In addition, the graphene-like two-dimensional materials with a multi-layer feature, MXene has a high dielectric loss in a polymer matrix at low percolation limit (15 wt%) [12].…”
Section: Introductionmentioning
confidence: 99%